PELATIHAN PENGGUNAAN TEKNOLOGI INFORMASI DI KAMPUNG YOKA KOTA JAYAPURA - N. O. Yanthy; A. R. Nurmaningtyas; S. Usman; Y L MARNALA SITORUS (JURNAL ABDIMAS DINAMIS : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
Many development programs have been carried out since the implementation of special autonomyin Papua, including the community driven development that was implemented in village. Thedevelopment activities in the village increased after the Village Fund transfer from the centralgovernment. However, there are not every village in Papua can take advantage of this opportunityproperly. For example, because the villagers could not make a report of responsibility for thedevelopment funds that they received, the funds were disbursed at a later stage by the government.To overcome this, the Head of Yoka Village then asked for help from higher education institutions.After take a pre-survey to Yoka Village, the institution then provides an initial solution by providingtraining in the use of information technology to the villagers. The training team consists of lecturerswho train in accordance with the abilities of each citizen. The training was conducted at the VillageOffice Hall and one participant received one trainer along with a computer facility during thepractice. Only a small number of participants attended because most villagers preferred farming. Itis different if the participants are given money, for example in lieu of transportation costs. The levelof participation of residents of Yoka Village is still in the category of participation due to materialincentives. However, for the few residents who were willing.